Kampo formula hochu-ekki-to (Bu-Zhong-Yi-Qi-Tang, TJ-41) ameliorates muscle atrophy by modulating atrogenes and AMPK in vivo and in vitro - Mitsutaka Yakabe; Tatsuya Hosoi; Hiroko Sasakawa; Masahiro Akishita; Sumito Ogawa (BMC, 2022)
Abstract Background Muscle disuse results in loss of skeletal muscle mass and function. Hochu-ekki-to (TJ-41; Bu-Zhong-Yi-Qi-Tang in Chinese) is an herbal medicinal formulation used to treat patients with frailty, fatigue and appetite loss. It has been suggested that two atrogenes, atrogin-1 and muscle Ring finger 1 (MuRF1), are ubiquitin ligases involved in disuse-induced muscle atrophy and that 5' adenosine monophosphate-activated protein kinase (AMPK) is involved in skeletal muscle metabolism. Effects of TJ-41 on disuse-induced muscle atrophy are unclear. Methods We subjected differentiated C2C12 myotubes to serum starvation, then examined the effects of TJ-41 on atrogenes expression, AMPK activity and the morphology of the myotubes. Male C57BL/6J mice were subjected to tail-suspension to induce hindlimb atrophy. We administered TJ-41 by gavage to the control group and the tail-suspended group, then examined the effects of TJ-41 on atrogene expression, AMPK activity, and the muscle weight. Results Serum starvation induced the expression of atrogin-1 and MuRF1 in C2C12 myotubes, and TJ-41 significantly downregulated the expression of atrogin-1. Tail-suspension of the mice induced the expression of atrogin-1 and MuRF1 in skeletal muscle as well as its muscle atrophy, whereas TJ-41 treatment significantly downregulated the expression of atrogin-1 and ameliorated the loss of the muscle weight. In addition, TJ-41 also activated AMPK and inactivated Akt and mTOR in skeletal muscle in vivo. Conclusion TJ-41 inhibited atrogenes in an Akt-independent manner as well as activating AMPK in skeletal muscles in vivo, further implying the therapeutic potential of TJ-41 against disuse-induced muscle atrophy and other atrogenes-dependent atrophic conditions.